Long-term Trends of PM2.5 Composition during Cold Seasons in Shanghai after Releasing Clean Air Action Plan - Ruoyan Wang; Xingnan Ye; Weijie Huang; Zhixiao Lv; Yinghui Yao; Fan Yang; Yinghua Liu; Juntao Huo; Yusen Duan (Aerosol and Air Quality Research)
Abstract Reducing PM2.5 pollution remains a great challenge during wintertime in Shanghai. Here, we investigated the long-term trends of aerosol composition and formation mechanism in the cold seasons of Shanghai from November 2014 to February 2020 using in-situ continuous hourly data. With the reduction of SO2 by 96% relative to 2014, the annual declines for SO2 and sulfate concentrations were 26.1% and 13.2%, respectively. In contrast to the great achievement in reducing SO2 emissions, the control of NOx was less effective because the effect of industrial denitrification on reducing NOx emissions was partially offset by the increase in the number of automobiles. As tracers of biomass burning and soil dust, the concentration of K+ and Ca2+ also declined quickly, indicating that open biomass burning and construction dust were effectively controlled. In contrast to a significant reduction of heavy and moderate pollution events, lightly polluted haze events remained high frequency in December and January, shedding light on pollution control in the future. The NO3−/SO42− ratio during the lightly polluted period was below 1.3 in 2014/2015 while it climbed above 2.5 in 2019/2020, indicating a distinct transition from the equal contribution of coal combustion and automobile exhaust to haze formation in 2014/2015 to nitrate-dominated in 2019/2020. The impact of inter-regional transport on Shanghai’s air quality has significantly weakened from 2014 to 2020. The contributions of local emissions and regional transport from the Channel of Suzhou-Wuxi-Changzhou to PM2.5 episodes have increased, suggesting that strengthening joint prevention and control in the Yangtze River Delta is the key to continuous improvement in air quality. NO2 was rapidly converted to nitrate under high relative humidity and an ozone-rich atmosphere, indicating that nighttime N2O5 hydrolysis dominated the nitrate explosive growth mechanisms. To coordinate the control of PM2.5 and O3 pollution, it is recommended to implement a renewable energy strategy for non-road mobile equipment in addition to promoting new energy vehicles.